From research to teaching : a guide to beginning your classroom career - Kibbe, Michael, 1980- (Downers Grove: Inter Vasity press, 2021)
"The transition from graduate studies to teaching is full of challenges. In this concise, practical guide for the aspiring professor, Michael Kibbe offers plenty of personal examples and tested advice as he covers preparation for teaching, best practices in the classroom, self-evaluation, and the discovery of your mission and method"--
Before the classroom: preparation -- In the classroom: execution -- After the classroom: reflection -- -- Mission and method -- Community -- Limitations -- Power.
Includes bibliographical references.
Keywords: First year teachers; College teaching; Religious educators; Teacher effectiveness; School-to-work transition